How do medical students define a Health Promoting Learning Environments? - Joffe, Rachel; Oczkowski, Veronica; Le, Diana; Lewis, Melanie; Do, Victor (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2025)
Background: Medical students in Canada report significantly higher rates of suicidal ideation, psychological stress, as well as mood and anxiety disorders, compared to age matched general population. We are still early in the process of having a comprehensive approach to learner wellbeing that centers around health promoting learning environments (HPLE) - focusing on more systemic actions as guided by the international Okanagan Charter. To move forward, we need to further understand what learners, faculty and staff view as critical components in an HPLE and explore how we can best advance efforts to create and embed HPLEs in medical education. The objectives of this study were to elucidate how medical students define an HPLE and what medical students perceive as the main barriers and facilitating factors to developing and fostering HPLEs.Methods: We undertook an exploratory qualitative study using virtual semi-structured interviews of how medical students define an HPLE and the facilitators and barriers of this. We used thematic analysis to review all transcripts with ongoing iterative analysis. Final themes were agreed on consensus.Results: We interviewed 14 medical students from all years at the University of Alberta. We identified four overarching themes which serve as important components of an HPLE including that HPLEs have foundational characteristics of respect, transparency, and open communication. Developing HPLEs require multi-pronged approaches that starts with ensuring basic needs are met and empowering learners to make health promoting choices. Learners identified that a culture of wellbeing is driven by wellbeing centered leadership. A safe space to take an active role in influencing their environment help learners thrive.Conclusions: Our study focused on elucidating medical student perspectives on factors that contribute to and foster a health promoting learning environment. Our findings can inform on systemic efforts to embed wellbeing into medical education in Canada.